Problematika Penerapan Quick Response Code Indonesian Sandard (QRIS) di Aceh (Studi Pada UMKM di Kota Banda Aceh) - Israk Ahmadsyah; Jalilah, Jalilah; Renail Rozy (Jihbiz: Global Journal of Islamic Banking and Finance, 2026)
The rapid development of information technology, especially FinTech, has led the dominance of digital finance in Indonesia through digital wallet applications and QR Code. QRIS, the non-cash payment standard of Bank Indonesia, facilitates transactions for consumers and merchants. In Banda Aceh UMKM sector, QRIS is growing rapidly, providing transaction facility but also facing challenges. The study aims to find out how the implementation of the Quick Response Code Indonesian Standard (QRIS) in the Small and Medium Small Enterprises (UMKM) sector in Banda Aceh City is problematic by showcasing the mechanisms of QRIS implementation, its positive impact on UMKM, and the challenges faced. The study uses a qualitative approach with descriptive analysis and the number of informants in the study as many as 17 informants. The research finds that while QRIS has a positive impact, there are barriers such as costs, internet connectivity, application technical problems, as well as a lack of customer improvement and benefits for UMKM. Solutions such as cost subsidies, better internet infrastructure, application updates, efficient time transactions between banks, and educational programmes are needed to address these challenges.